Estudio de prefactibilidad para la instalación de una planta de procesamiento de chocolate bitter orgánico en barra - Paucar Quispe, Andrea Pilar (2020)
The present study evaluates the economic, technological, financial, social and market feasibility for the installation of a 65% premium organic chocolate bar processing plant, fine aroma, with dehydrated forest fruits for the Metropolitan Lima´s market. This product will be called “Amora Chocolate” and will be sold at a price of 15 soles to the final consumer in the presentation of a 50 gram tablet containing the content of a bitter chocolate bar with pieces of blueberries and dehydrated raspberries, which they will be distributed in specialized stores, supermarkets and auto services of Metropolitan Lima. The target market of the product which will be distributed of the inhabitants of Modern Lima, who belong to the A / B socioeconomic levels and are between the ages of 18 and 55, obtaining a project demand of 425,820 bars of Premium organic chocolate bars for the first year of the project. On the other hand, through a plant location analysis it was determined that the best location is in the department of Lima, in the district of Pachacamac, with a land requirement of 350 m². The plant size for this project will be 670,580 units of finished product by 2024 and will be limited by the Point of equilibrium as a lower limit and as an upper limit for the productive resource; Likewise, it was determined that the process bottleneck would be the refining machine. Finally, the implementation of a premium organic chocolate processing plant with dehydrated fruits requires a total investment of approximately S/. 1,668,678.